Mixed-species association among malaysian primates during the covid-19 outbreak in Genting Highlands, Peninsular Malaysia - Badrul Munir, Md Zain; Mohd Ridwan, Abd Rahman; Hani Nabilia, Muhd Sahimi; Muhammad Abu Bakar, Abdul Latiff; Eddie, Chan (Penerbit UMT, 2021)
This is the first report to elucidate primate mixed-species association during Covid-19 outbreak in Malaysia. The observations were carried out at Genting Highlands between 14-24th April 2020 using ad libitum sampling. Five Genting Highlands primate species were observed at approximately 66 observation hours which include Symphalangus syndactylus (siamang), Trachypithecus obscurus obscurus (dusky langur), Presbytis siamensis siamensis (Malayan pale-thighed surili), Macaca nemestrina (southern pig-tailed macaque), and Macaca fascicularis (long-tailed macaque). Primates in Genting Highlands were seen interacting among themselves during the third phase of the MCO. Siamangs, dusky langurs, and long-tailed macaques were observed sharing space and interacting in an old section of Genting View Resorts that is currently under renovation. Malayan pale- thighed langurs were also observed approaching this area. During the third phase of the MCO, siamangs, dusky langurs, long-tailed macaques, and pig-tailed macaques consumed fruits of the fig tree (Ficus benjamina), which last for only one week. Strict controls on public movement are believed to have created environmental conditions that enabled Genting Highlands primates to move and interact freely among themselves.